Low complexity uplink SFBC-based MIMO-SCMA joint decoding algorithm - Wu, Zhanji; Zhang, Chen; Shen, Xia; Jiao, Huiying (2017 3rd IEEE International Conference on Computer and Communications (ICCC), 2017)
Sparse code multiple access (SCMA) is a non-orthogonal multiple access scheme, which has been considered as one of the key technologies of the fifth generation (5G) to accommodate massive connectivity. Moreover, the application of multiple-input multiple-output (MIMO) technique to SCMA systems is an important research direction in 5G development. However, detectors of this type of system have high computational complexity. In this paper, a space-frequency block code (SFBC) based MIMO-SCMA system is considered, and we propose a decoding algorithm for the MIMO-SCMA system, which have a close block error rate (BLER) performance to message passing algorithm (MPA) and lower computational complexity. The proposed decoding algorithm, called Partial-Decoding-MPA (PD-MPA), could dynamically remove the number of combinations used in the update at resource nodes to reduce decoding complexity. Simulation results show that the proposed detector can decrease the complexity significantly with slight BLER performance loss.